SISTEM PENGUKURAN KINERJA : TINJAUAN DALAM MENINGKATKAN KINERJA USAHA MIKRO KECIL DAN MENENGAH - Galih Fajar Muttaqin (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Management functions consisting of planning, coordinating, directing and controlling are carried out by managers in order that the success of corporate management can be achieved in accordance with the intended purpose. Such success can be seen through performance. This research intends to analyze the influence of performance measurement system, management control system to performance.This research uses quantitative method which the data obtained through spreading of questioner with purposive sampling method. Data analysis is done by using PLS software.The results of this study indicate that (1) Performance Measurement System influences the Management Control System (2) Management Control System affects the performance.